Parâmetros genéticos em progênies de açaizeiro na fase juvenil - Andrade, Patrícia Cardoso (2016)
Evaluation and characterization of different progenies of assai palm (Euterpe oleracea) for juvenile traits can help the selection at earlier stages of superior genotypes for fruit yield. The aim of this study was to estimate genetic parameters and to select progenies and individual plants of assai palm for juvenile traits. We evaluated 34 half-sib progenies,16 full-sib progenies and two checks in an experiment in a completely randomized design with eight repetitions and one-tree plot. The following traits were assessed: number of leaves (NL), number of emitted leaves (NEL), number of dead leaves (NDM), total length of the leaf (TLL), length of leaf sheath (LLS), plant height (PH) circumference of the girth (CG), number of leaflets pairs (NLP) and number of tillers (NT) in five measurements. The data analysis was performed by mixed model approach using the restricted maximum likelihood method. We obtained the predictions of additive genetic values of the progenies and individual plants, estimated the selective accuracy and the selection gain. Significant genetic variance was only observed among full-sib progenies of E. oleracea, except for NT. In the full-sib progenies most of traits presented high accuracy, except for NT. The progeny mean heritabilities ranged from 51% (NDM) to 59% (LLS). The genetic correlations were positive and moderate among most of juvenile traits. The genetic gains were significant for traits PH, LLS and CG. The progenies P42, P33 and P37 were promising for breeding purposes of assai palm and allowed to identify superior plants.